IMPLEMENTATION OF AN ELECTRICAL POWER BASICS E-MODULE TO IMPROVE STUDENT LEARNING OUTCOMES IN VOCATIONAL HIGH SCHOOLS - Noviani Noviani; Taali Taali; Titi Sriwahyuni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to describe the extent to which student learning outcomes improved after the implementation of the Basic Electrical Engineering e-module in vocational learning. This study used a pre-experimental design with a one-group pretest–posttest model, involving 32 tenth-grade students of the Electrical Power Installation Engineering expertise program at SMKN 4 Palembang. Data were collected using multiple-choice pretests and posttests that assessed students' conceptual understanding of Basic Electrical Engineering. The e-module was designed with multimedia elements like text, audio, and worksheets to support flexible, independent learning. The results showed a significant improvement in student learning performance, with the average pretest score increasing from 68.9 to 81.1 and an N-Gain value of 0.392, which is included in the moderate category. These findings indicate that the e-module effectively improves student understanding and engagement, while confirming its pedagogical potential in vocational education. The novelty of this study lies in its focus on e-modules for technical-vocational subjects, which can foster conceptual mastery in specific technical materials. This research contributes to the development of literature on technology-based learning and confirms the potential of e-modules as a vocational education innovation.